Modern options for financing real estate investments - Silviu Cornel Chiriac (Agora International Journal of Economical Sciences (AIJES), 2021)
The realities of the period we live in with limited resources, uncertainties, speculations, radical upheavals, put their mark on the entities in many respects. The situation requires a rethinking of the business so that it can remain viable, to meet the needs of customers and to obtain a maximum profit. The decision-making process is one that thus outlines the major importance it has for each entity. The options that the entity can use to finance its investments are the objective of this material, our analysis aims to present the main characteristics of these options.
Keywords: 330